2018
DOI: 10.1097/md.0000000000010864
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of photodynamic therapy for cervical intraepithelial neoplasia and human papilloma virus infection

Abstract: PDT that targets CIN or cervical HPV infection improves the CRR, but slightly compromises safety. Further studies are necessary to identify the most effective and least toxic photosensitizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 35 publications
1
36
0
12
Order By: Relevance
“…However, there is an urgent need to develop effective approaches to treat peritoneal carcinosis of ovarian origin. Photodynamic therapy (PDT) has been used in many areas, including the treatment of cutaneous and pleural diseases [9]. In fact, several clinical trials have detailed the use of this therapy in skin cancer [10] or Glioblastoma [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is an urgent need to develop effective approaches to treat peritoneal carcinosis of ovarian origin. Photodynamic therapy (PDT) has been used in many areas, including the treatment of cutaneous and pleural diseases [9]. In fact, several clinical trials have detailed the use of this therapy in skin cancer [10] or Glioblastoma [11].…”
Section: Introductionmentioning
confidence: 99%
“…PS photoactivation is a well-established therapeutic approach used to promote cell killing based on the interaction between visible light and matter [1,2]. The use of PS drugs in the clinic is termed “photodynamic therapy” (PDT), which is successfully targeted to cutaneous cancers, infections, and other pathologies [3,4,5,6,7]. In PDT, wavelength-selective light exposure of cells loaded with a PS promotes the inert PS molecule to a relatively long-lived excited state in which it interacts with molecular oxygen (O 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The complete remission of lesions totalized 57.14%, of which 21.43% presented at the follow up of one year and 35.71%at two years. In a systematic review and meta-analysis by Zhang et al, they concluded that PDT showed more significant results in eradicating premalignant lesions (282 patients) than the placebo group (141 patients) [15].…”
Section: Resultsmentioning
confidence: 99%
“…In this study we were also able to follow 14 patients for two years from the placebo group, where eight received only irradiation at 80 J/cm 2 and six patients received only cream containing 20% Methyl aminolevulinate (MAL) in the cervix for one hour. It seems to be a low number of patients in the placebo group, but other authors who work in gynecological PDT and also in the treatment of low- and high-grade CIN report that their placebo groups are in a smaller number than the treatment group and it is known that a significant difference between these two groups is not expected, especially for CIN 1 treatment once most of CIN 1 lesions disappear naturally [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation